Strategi Kepala Sekolah dalam Meningkatkan Kualitas Bacaan Al-Qur’an Siswa di SMP Muhammadiyah 57 Medan - Bayu Wibowo; Abd. Rahman (PT. ALHAFI BERKAH INDONESIA, 2023)
The purpose of this research is to find out the head strategy schools in improving the quality of Al-Qur'an reading in Muhammadiyah Middle Schools 57 Medan. In this study, researchers used a type of qualitative research. This research was conducted by collecting data, namely through: Interviews, Observation and Documentation. The research results obtained are reading extracurricular activities This Qur'an runs smoothly and conducively. Extracurricular Activities Reading the Qur'an is also very important to be implemented first in the digital era which requires educational institutions to reproduce religious activities to help students at this time for more understand Islamic teachings.